Taxomony and mycorrhizal ecology of the desert truffles in the genus Terfezia - Alsheikh, Abdulmagid M.
Mycorrhizal fungi in arid and semiarid rangelands have received little study in southwest Asia and north Africa, although they are important in food production and rangeland productivity. The desert truffles of the genera Terfezia and Tirmania form fruiting-bodies and mycorrhizae with rangeland plants. This thesis treats the taxonomy and the ecology of the genus Terfezia. A second part describes experimental studies of the mycorrhizal associations between two Tirmania and two Terfezia spp. and six annual and perennial spp. of Cistaceae. Terfezia has been found in all continents except Australia and Antarctica. Most species and specimens have been collected from north Africa to west and southwest Asia and southern Europe. Terfezia is characterized by smooth, brown to dark brown ascomata with a gleba of brown, fertile, globose to elongated pockets separated by paler, sterile but otherwise undifferentiated tramal veins; globose to subglobose, reniform or saccate asci with (3-) 5-8 (14) spores; and mostly globose, hyaline to golden brown spores prominently ornamented with spines, rods, cones, warts, papillae or reticula. Before this study, names had been proposed for 57 species, 9 varieties and 1 form within the genus Terfezia. This work retains 18 species and no varietal names. No collections were located of one species and five synonyms. Three new species are provisionally proposed. Most Terfezia species are widespread in desert habitats and rangelands except T. gigantea and T. terfezioides which grow in northern temperate, mesic forests. Spores of species growing in deserts are apparently dispersed by the abrasion of exposed ascomata, dried in-situ, by wind-blown sand or other storm systems. Desert animals may also participate in spore dispersal. Some Terfezia spp. have been demonstrated to form mycorrhizae with annual and perennial Helianthemum and other Cistaceae spp., and the mycorrhizal habit may be assumed for all. Mycorrhizae of 4 species of desert truffles and 6 annual and perennial species of Cistaceae ...